A conceptual framework for customers' loyalty in mobile loyalty programmes / Sharlini Seridaran and Mohd Nazri Mohd Noor - Seridaran, Sharlini; Mohd Noor, Mohd Nazri (UiTM Press, 2021)
The increasing number of academic studies on customer loyalty shows the evolution of customer behavior and the diversity of business offerings. The main purpose of this study is to examine existing academic pieces of literature. The articles discovered are from the last ten years and elaborate on the importance of customer loyalty within the established mobile loyalty programmes. As businesses evolve, the importance of developing long-term relationships with customers becomes increasingly important. This explains the recent trend of loyalty programmes in other industries. This paper aims to establish a conceptual framework that focuses on customer loyalty. Furthermore, the Theory of Planned Behavior is used as a core element to better understand customers' intentions to accomplish a certain behavior in the hope that the actions favor businesses. Customer attitude, subjective norms, and customer satisfaction were identified as common antecedents in the literature. The recommended framework in this study may serve as a reference point for practitioners looking to improve current marketing strategies, particularly those focusing on mobile loyalty programmes. This is done to keep businesses up to date on current needs and trends.